Application Analysis and Problem Prevention of Cast-in-Situ Beamless Hollow Floor Construction Technique in Large Deep Foundation Pit. Issue 3 (April 2021) - Ou, Yazhou; Chen, Gang; Xing, Cheng; Jin, Shulou
Abstract: Cast-in-place concrete beamless hollow floor is more and more widely used in engineering, especially in basement engineering, due to its characteristics like increase of the structure height, enhancement of heat preservation, heat insulation, noise reduction, rapid construction speed and others. Based on engineering practice, the application of cast-in-situ beamless hollow floor cover in large deep foundation pit is studied. In order to improve the construction quality, the deformation and stress state of long-span hollow plate are analyzed by finite element simulation. By optimizing and improving the process and comparing the results, the process method which is helpful to improve the quality of finished products of beam-less floor under this condition is extracted.